Abnormal expression of TSG-6 disturbs extracellular matrix homeostasis in chondrocytes from endemic osteoarthritis - Ning, Yujie; Zhang, Pan; Zhang, Feiyu; Chen, Sijie; Liu, Yanli; Chen, Feihong; Wu, Yifan; Li, Shujin; Wang, Chaowei; Gong, Yi; Hu, Minhan; Huang, Ruitian; et al. (Frontiers in Genetics, 2022)
Background and aims: Kashin-Beck disease (KBD) is a unique endemic osteochondropathy with unclear pathogenesis in China. T-2 toxin exposure has been identified a significant risk factor of KBD. However, the mechanism of articular cartilage damage induced by T-2 toxin is a conundrum. We aimed to explore the role of extracellular matrix related gene TSG-6 in articular chondrocyte damage process under the exposure of HT-2 toxin. Methods: TSG-6 was identified as candidate gene by mining our previous gene expression profiling of KBD and verified by qRT-PCR and immunohistochemistry. Then, TSG-6 was silenced by RNA interference technology and overexpressed induced by TNF-α respectively. Gradient concentrations of HT-2 toxin were added to intervene C28/I2 chondrocytes. MTT was used to observe the proliferation and cell viability of chondrocytes, qRT-PCR was applied to detect the expression changes of MMP1, MMP3, MMP13, COL2A1 and proteoglycan before and after treatments for verification. Results: TSG-6 was upregulated in KBD chondrocytes at mRNA and upregulated in the superficial, middle and deep zone of KBD cartilage. After TSG-6 silencing, the expressions of MMP1, MMP3, MMP13 and proteoglycan were significantly decreased while COL2A1 expression was significantly increased, which was reversed after the overexpression of TSG-6 induced by TNF-α (P<0.05). The survival rate of chondrocytes correspondingly reduced with the increase of HT-2 toxin concentration. Compared with the blank control group, the expression of the MMPs was increased in the intervention group of HT-2 toxin, while the expression of proteoglycan and COL2A1 was decreased (P<0.05). Conclusions: The upregulation of TSG-6 gene may have a role in promoting the damage and the degradation of extracellular matrix in KBD chondrocytes under the exposure of HT-2 toxin.